Perubahan Profil Kemiskinan Masyarakat Pasca Pendaftaran Tanah Sistematis Lengkap: Pendekatan Aset Penghidupan - Augustina, Prasetya Hanif; Pujiriyani, Dwi Wulan; Farid, Abdul Haris (Sekolah Tinggi Pertanahan Nasional, 2024)
Complete Systematic Land Registration or PTSL is a program that aims to provide legal certainty and legal protection of land rights owned by the community so that it can improve the welfare and prosperity of the community. This paper aims to see the impact of PTSL through community livelihood assets. This article will answer the problem: What is the impact of the PTSL program on community asset management in Karangwangi Village? and What is the potential of the PTSL program in changing the poverty profile of the community in Karangwangi Village? This paper focuses on analyzing the livelihood assets of PTSL participating communities in Karangwangi Village, Depok District, Cirebon Regency. This research uses quantitative and qualitative methods to obtain data related to livelihood assets. The quantitative method was carried out through a survey of 94 respondents, using a questionnaire which was then analyzed using the livelihood asset pentagon. For the qualitative method, it was carried out through interviews with respondents. The results of the research show that there has been a change in the management of community assets from being productive to being both productive and consumptive. There was an increase in 3 (three) of the 5 (five) livelihood assets, namely natural assets, physical assets and financial assets. The PTSL program opens access to financial institutions. The poverty profile experiences change due to people's ability to not only meet minimum living needs (survival) but also social needs and accumulate capital. Pendaftaran Tanah Sistematis Lengkap atau PTSL merupakan program yang bertujuan untuk memberikan kepastian hukum dan perlindungan hukum hak atas tanah yang dimiliki oleh masyarakat sehingga dapat meningkatkan kesejahteraan dan kemakmuran masyarakat. Tulisan ini bertujuan untuk melihat dampak PTSL melalui aset penghidupan masyarakat. Tulisan ini akan menjawab permasalahan: Bagaimana dampak program PTSL pada perubahan pengelolaan aset masyarakat di Desa Karangwangi? serta Bagaimana potensi program PTSL dalam mengubah profil kemiskinan masyarakat di Desa Karangwangi?. Tulisan ini memfokuskan analisis aset penghidupan masyarakat peserta PTSL di Desa Karangwangi, Kecamatan Depok, Kabupaten Cirebon. Penelitian ini menggunakan metode kuantitatif dan kualitatif untuk mendapatkan data terkait aset penghidupan. Metode kuantitatif dilakukan melalui survei terhadap 94 responden, menggunakan kuesioner yang selanjutnya dilakukan analisis menggunakan pentagon aset penghidupan. Untuk metode kualitatif, dilakukan melalui wawancara terhadap responden. Hasil penelitian menunjukkan bahwa terdapat perubahan pengelolaan aset masyarakat dari yang semula produktif, menjadi produktif sekaligus konsumtif. Terdapat peningkatan pada 3 (tiga) dari 5 (lima) aset penghidupan yaitu aset alam, aset fisik dan aset finansial. Program PTSL membuka akses terhadap lembaga keuangan. Profil kemiskinan mengalami perubahan dari kemampuan masyarakat yang tidak hanya mampu memenuhi kebutuhan hidup minimum (survival) tetapi juga kebutuhan sosial dan penumpukan modalnya.